Implementing Strategic Communication Training to Overcome Student’s Speaking Difficulties in English Among Eight Grade Students at SMPN 1 Krejengan - Novita Agustinningsih; Fery Ferdianto; Zainuddin (LPPM Universitas PGRI Semarang, 2026)
Many EFL students at the junior high school level struggle with communication breakdowns due to limited vocabulary and high anxiety, yet traditional speaking instructions often overlook the explicit teaching of strategic competence. This study aims to examine how Strategic Communication Training can help EFL students at SMPN 1 Kerejengan overcome speaking difficulties, focusing on improving their ability to manage communication breakdowns, enhance fluency, and increase confidence. This study employed a qualitative case study design, with data collected through semi-structured interviews, classroom observations, and document analysis, and analyzed using thematic analysis. The findings reveal that Strategic Communication Training significantly improved students’ speaking fluency, confidence, and interaction ability. Students demonstrated effective use of strategies such as paraphrasing, circumlocution, clarification requests, and confirmation checks. Classroom participation also increased through role-plays and group discussions, while students became more capable of maintaining conversations despite linguistic limitations and showed reduced speaking anxiety. This study is applicable in EFL classrooms, particularly in junior high schools and teacher education programs, providing practical insights for curriculum developers. The novelty of this study lies in integrating Strategic Communication Training into classroom-based speaking instruction, offering new insights into how strategic competence can enhance students’ communicative proficiency and overall engagement in EFL learning.